2018
DOI: 10.1111/ppc.12324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity Program on cognitive function and sleep quality in elderly with mild cognitive impairment: A randomized controlled trial

Abstract: Aim The aim of this study is to determine the effect of a 20‐week Physical Activity Program for elderly individuals with mild cognitive impairment (MCI) on their cognitive functions and sleep quality. Methods A randomized controlled trial research design was used in this experimental pretest‐posttest study. The data were analyzed using SPSS 21.0. Results This study showed that the Physical Activity Program improved the cognitive functions and sleep quality of elderly individuals (p < 0.05). Conclusion and Prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 35 publications
0
62
0
1
Order By: Relevance
“…There is a lot of research evidence that physical activity reduces the risk of many noncommunicable diseases, including cancer, coronary diseases, diabetes, and pulmonary diseases [4,5,6]. Regular physical activity can also improve mental health, cognitive functions, and overall well-being [7,8,9,10]. Many studies have confirmed that people that are more physically active have a lower rate of overall mortality [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There is a lot of research evidence that physical activity reduces the risk of many noncommunicable diseases, including cancer, coronary diseases, diabetes, and pulmonary diseases [4,5,6]. Regular physical activity can also improve mental health, cognitive functions, and overall well-being [7,8,9,10]. Many studies have confirmed that people that are more physically active have a lower rate of overall mortality [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…While more than one-third of the interventions were beneficial, 14 out of 26 controls significantly decreased. Descriptions of intervention and control groups included in the review are presented in Table 3 [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54]. All of the included studies were considered to have had a good methodological quality, scoring between 7 and 9 points according to the PEDro.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…[4][5][6]. Regular physical activity could also improve mental health, cognitive functions and overall well-being [7][8][9][10]. A lot of studies confirmed that people that are more physically active have a lower rate of overall mortality [11,12].…”
Section: Introductionmentioning
confidence: 99%